Learning – a starting point - Boehm, Jan (Journal of Education in Black Sea Region, 2022)
Pedagogical and didactic efforts are usually based on the premise that learning takes place under favourable conditions. However, these conditions already presuppose what is supposed to take place: learning. This article deals with the basic mechanisms of learning, identifying, so to speak, the foundation of any pedagogical endeavour. For this, one of the earliest texts in pedagogy is used, Plato’s Allegory of the Cave. On top of the philosophical reflection, consequences for pedagogical practice are drawn.